2017
DOI: 10.22146/ifnp.24278
|View full text |Cite
|
Sign up to set email alerts
|

Production and Application of Lactobacillus plantarum IBL-2 Bacteriocins as Meat Product Biopreservatives

Abstract: Bacteriocin produced by Lactic Acid Bacteria (LAB) is a potential candidate for biopreservatives, which is safe for consumption, since it can be degraded by proteolytic enzymes. The aim of this study was to optimize bacteriocin production from Lactobacillus plantarum IBL-2 and to evaluate the effectiveness of bacteriocins in decreasing the total number of several tested bacteria using total plate count method and Salmonella typhimurium spiked in ground beef. Bacteriocin was produced through fermentation of L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…It does not kill all microorganisms but only inhibits their growth. The TPC in this study with the addition of 0.5% bacteriocin to sausages stored for six days (5.20 x 10 4 CFU/mg equivalent to 4.71 log CFU/g) was lower than the research [24], who added supernatant bacteriocin from L. plantarum IBL-2 to fresh ground meat and stored it for six days. The low TPC in this study was due to the bacteriocin being applied to sausages, which were made through a steaming process.…”
Section: Total Plate Countcontrasting
confidence: 65%
“…It does not kill all microorganisms but only inhibits their growth. The TPC in this study with the addition of 0.5% bacteriocin to sausages stored for six days (5.20 x 10 4 CFU/mg equivalent to 4.71 log CFU/g) was lower than the research [24], who added supernatant bacteriocin from L. plantarum IBL-2 to fresh ground meat and stored it for six days. The low TPC in this study was due to the bacteriocin being applied to sausages, which were made through a steaming process.…”
Section: Total Plate Countcontrasting
confidence: 65%
“…Total aerobic bacteria in sausages with B3L3 treatment were higher compared to the results of Wibowo et al (2017) showed that the addition of the bacteriocin supernatant from L. plantarum IBL-2 to fresh ground beef and stored for 12 days had total aerobic bacteria of 0.96 x 10 4 CFU / ml. Because L. plantarum IBL-2 of Wibowo research added with nisin amide.…”
Section: Total Aerobic Bacteriamentioning
confidence: 64%